Diagnosis of postpartum depression and associated factors in South Africa: a cohort study of 47,697 women - C. Gastaldon; V. Whitesell Skrivankova; G. Schoretsanitis; N. Folb; K. Taghavi; M. A. Davies; M. Cornell; G. Salanti; C. Mesa Vieira; M. Tlali; G. Maartens; M. Egger; et al. (Epidemiology and Psychiatric Sciences, 2025)
Abstract Aims About one-third of South African women have clinically significant symptoms of postpartum depression (PPD). Several socio-demographic risk factors for PPD exist, but data on medical and obstetric risk factors remain scarce for low- and middle-income countries and particularly in sub-Saharan Africa. We aimed to estimate the proportion of women with PPD and investigate socio-demographic, medical and obstetric risk factors for PPD among women receiving private medical care in South Africa (SA).